Emerging Role Of Magnesium In Modern Anaesthesia, Analgesia, Obstetrics & Critical Care. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Magnesium is a ancient cation but it can be used successfully as adjuvant to Local  anaesthetic agent.iIt can be used successfully in various Surgeries like neurosurgery,  cardiac surgery,as induced hypotensive agent,in FESS Surgeries, used for attenuation of  pressure response to laryngoscopy& intubation,also to prevent postoperative sore throat.It  can be used in critical care,& in obstetrics to prevent Eclampsia.In present article various  uses of Magnesium sulfate discussed.
Keywords: Magnesium; laryngoscopy& intubation; critical care,& in obstetrics